Dietary clove (Syzygium aromaticum) powder enhanced broiler chicken performance, gut histomorphometry and health-associated whilst decreasing pathogenic microbiota - Ogwuegbu, M. C.; Uzochukwu, I. E.; Edeh, H. O.; Ukah, E. G.; Obey, C. O.; Okpanachi, U.; Mthiyane, D. M. N. (Journal of the Indonesian Tropical Animal Agriculture, 2025)
This study evaluated the impact of dietary clove powder on growth performance, carcass traits, nutrient digestibility, jejunal histomorphometry and ileal microbiota in broiler chickens. A total of 250 Chikun day-old broiler chicks were allocated to 5 dietary groups with 5 replicates of 10 birds each for 6 weeks in a completely randomized design. The groups were fed diets containing clove powder at 0, 0.5, 1.0, 1.5 and 2 g/kg diet. Results showed that dietary clove supplementation improved final body weight and feed conversion ratio (P < 0.001) while reducing total feed intake. Also, it increased weights of live chickens at slaughter, breast meat, shank and drumstick/thigh ratio (P < 0.001). Further, it linearly increased apparent digestibility of DM, CP, and EE (P < 0.01) as it quadratically decreased CF (P < 0.01). Furthermore, it linearly increased jejunal villus length, crypt depth and thickness of muscularis (P < 0.001) whilst it quadratically decreased thickness of the epithelium (P < 0.01). Moreo-ver, it increased ileal Lactobacilli whilst decreasing Salmonella and E. coli (P < 0.05) bacterial species. In conclusion, dietary clove powder improved growth performance, carcass characteristics, nutrient digestibility, gut histomorphometry and Lactobacilli while it decreased Salmonella and E. coli bacteria.